1987
DOI: 10.1002/j.1460-2075.1987.tb02492.x
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic vesicles in electromotoneurones. I. Axonal transport, site of transmitter uptake and processing of a core proteoglycan during maturation.

Abstract: We were able by using an in vivo pulse‐label technique to trace part of the life cycle of a secretory organelle, the acetylcholine‐storing synaptic vesicle from electromotoneurones of Torpedo marmorata. This technique uses [35S]sulphate incorporation into the cell bodies of the electromotoneurones which results in radioactive labelling of a synaptic vesicle heparansulphate proteoglycan–a major core component. Vesicles are anterogradely transported in the axons at a fast rate as ‘empty’ organelles (VP0 populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 37 publications
5
20
0
Order By: Relevance
“…Tor 70 immunoreactivity did not migrate as a discrete band but instead was found as a broad smear between 90 and 200 kDa because of heterogeneity ofthe glycan moiety and/or proteolytic cleavage (23). Trypsin eliminated the 17-kDa VAMP-1 immunoreactive band in both intact and lysed vesicles, whereas the Tor 70 antigen was digested only if the vesicles were lysed before incubation with trypsin.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Tor 70 immunoreactivity did not migrate as a discrete band but instead was found as a broad smear between 90 and 200 kDa because of heterogeneity ofthe glycan moiety and/or proteolytic cleavage (23). Trypsin eliminated the 17-kDa VAMP-1 immunoreactive band in both intact and lysed vesicles, whereas the Tor 70 antigen was digested only if the vesicles were lysed before incubation with trypsin.…”
Section: Resultsmentioning
confidence: 98%
“…Most of the protein was eluted at positions flanking the immunoreactivity: fractions [22][23][24][25][26] contained 65% of the protein loaded onto the column, and another 10% was eluted in fractions 38-42. These data show that VAMP-1 fusion-protein immunoreactivity copurifies with synaptic vesicles.…”
Section: Resultsmentioning
confidence: 99%
“…This Torpedo protein has been also localized to intracellular membranes, including synaptic vesicles ( Ngsee and Scheller, 1989). Several proteoglycans associated with synaptic vesicles and membranes in Torpedo have been characterized (Kiene and Stadler, 1987;Carlson and Wight, 1987). Recently, it has been reported that the acetylcholine transporter-vesamicol receptor complex ( AcChT-VR) of Torpedo synaptic vesicles is associated with a KSPG (Bahr et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Secretory organelles are often isolated as a single fraction by density gradient centrifugation or other purification steps and are subsequently treated as a single population although they may be heterogeneous with regard to their composition depending on their functional state (Zimmermann and Denston, 1977) and the stage they may have reached within their life cycle. In the case of the acetylcholine-storing synaptic vesicles from Torpedo electromotoneurones, the physical separation of the site of secretory activity and the site of biosynthesis of the granules and, in addition, the relatively slow time-course of axonal transport and nerve terminal maturation as compared to mammalian secretory systems, has allowed us to demonstrate that the well-known resting and reserve populations of vesicles are preceded by and derived from empty, immature vesicles supplied by axonal transport from the cell body (Kiene and Stadler, 1987). There are thus at least three populations of vesicles in the nerve terminal.…”
Section: Introductionmentioning
confidence: 99%